TRIPLE ANTIHYPERTENSIVE THERAPY: FOCUS ON EFFICACY AND PROGNOSIS - O. D. Ostroumova; A. I. Kochetkov; A. V. Starodubova; I. V. Goloborodova; E. A. Smolyarchuk (Рациональная фармакотерапия в кардиологии)
In the article, with regard to current clinical recommendations, the place of combined antihypertensive therapy, especially triple drugs regimens, is considered in the treatment of patients with arterial hypertension. Special focus is given to the body of evidence for the efficacy of valsartan and amlodipine, as the reference drug of angiotensin II receptor blockers and calcium channel blockers, respectively. Not only their high antihypertensive properties are demonstrated, but also a favorable effect on target-organ protection and prognosis is described. In particular, the possibilities of valsartan in reducing the severity of left ventricular hypertrophy and microalbuminuria are described, and its unique properties in the class of sartans that allow the use of this drug in patients with ischemic heart disease and chronic heart failure are emphasized. Data on the antiatherosclerotic effects of amlodipine and its proven ability to reduce cardiovascular risk are presented. Current data are presented about their use in a fixed-dose combination with hydrochlorothiazide, including real clinical practice settings. The evidence base of high clinical efficacy, safety and metabolic neutrality of the triple combination of antihypertensive drugs valsartan, amlodipine and hydrochorothiazide is presented. The issues of increasing adherence of patients to treatment when prescribing fixed-dose combinations are considered. An algorithm for the selection of antihypertensive drugs in the form of monotherapy and combination therapy of two or three drugs depending on the clinical situation (the presence of certain target-organs damages and associated clinical conditions, primarily ischemic heart disease, atherosclerosis of carotid arteries and chronic heart failure) and the severity of the additional risk of cardiovascular complications.